New information on Bonapartenykus (Alvarezsauridae: Theropoda) from the Allen Formation (middle Campanian-lower Maastrichtian) of Río Negro Province, Patagonia, Argentina clarifies the Patagonykinae body plan - Jorge Gustavo Meso; Jonah Nathaniel Choiniere; Mattia Antonio Baiano; Stephen Louis Brusatte; Juan Ignacio Canale; Leonardo Salgado; Diego Pol; Michael Pittman (PLoS ONE, 2025)
Alvarezsauria is a group of morphologically distinctive, medium- to small-sized later-diverging coelurosaurian theropod dinosaurs, whose record ranges from the Late Jurassic to the Late Cretaceous. This clade had a widespread distribution in Laurasia in what is now Europe, Asia, and North America, although there are also several Cretaceous taxa from Gondwana in what is now Argentina that all belong to the family Alvarezsauridae. Although alvarezsaurid taxonomic diversity and anatomical knowledge has expanded over the last decade, alvarezsaurid internal phylogenetic relationships remain highly debated. In this contribution, we describe new alvarezsaurid material and review previously reported alvarezsaurid specimens from the middle Campanian—lower Maastrichtian Allen Formation discovered at the Salitral Ojo de Agua locality in Río Negro province, Patagonia, Argentina. Although these specimens were collected at different times without precise original provenance information, here we gathered X-ray diffraction data of the associated sediments that now suggests that all of these specimens come from the same site and stratigraphic level as the holotype of the alvarezsaurid Bonapartenykus ultimus. Based on this new provenance information and the morphological similarity of the considered specimens, here we tentatively refer them to the genus Bonapartenykus. These newly referred specimens add to the record of this genus and shed light on the body plan of the alvarezsaurid clade Patagonykinae by permitting a more complete reconstruction of the neck, pectoral girdle, hindlimb, and tail.